Value stream mapping: food supply chains in India and Bangladesh - Dora, Manoj; Veettil, Prakashan Chellattan (2022)
Working across South Asia, the CGIAR research initiative ‘Transforming Agrifood System in South Asia (TAFSSA)’ aims to deliver a coordinated program of research and engagement across the food production–to–consumption continuum to support equitable access to sustainable healthy diets, improve farmer livelihoods and resilience, and conserve land, air and groundwater resources. This transdisciplinary research seeks to map the impact of food waste across the different stakeholders in the food supply chains in India and Bangladesh using ‘lean thinking’ principles. In so doing, a sustainability performance matrix will be developed for encapsulating the economic, social, and environmental indicators as well as key performance indicators (KPIs) for identifying, assessing and benchmarking food waste across the food supply chains. The holistic sustainability performance matrix will help guide industry and policymakers to better understand the external costs of food waste and enable different stakeholders along the value chain to manage food waste more effectively. The new sustainability dimension of mapping the impact of food waste will contribute to both academic knowledge and improving industrial performance.